Respon pertumbuhan tanaman kacang hijau (vigna radiata l.) terhadap paparan cahaya matahari - yusti, lutfah dwita kurnia (Maliki Interdisciplinary Journal, 2025)
Sunlight is the main abiotic factor that is needed by plants to carry out their physiological functions. This study aims to describe the growth response of mung bean plants (Vigna radiata L.) to variations in sunlight intensity. The approach used is qualitative descriptive, with direct observation of plant morphological parameters such as stem height, number of leaves, and leaf color in three light intensity groups: high (±100%), medium (±60–70%), and low (±30–40%). The results of the observations showed that plants that received full light had more optimal vegetative growth, characterized by greater plant height, more leaves, and dark green leaf color. In contrast, plants that grew at medium and low light intensities showed adaptation characteristics such as leaf widening and stem elongation, but with lower growth effectiveness. These findings indicate that light intensity is an important factor in supporting the efficiency of photosynthesis and morphological development of mung beans. This study is expected to be a reference for more efficient and adaptive mung bean cultivation to environmental conditions.